α- Amylase inhibitory activity of Argyreia nervosa (Burm. f .) Bojer a medicinal plant in southern western ghats (International Journal of Food and Nutritional Sciences, 2022)
A. nervosa plant have been historically ascribed an important role in the traditional ayurvedic systems of holistic health and herbal medicine of the east. It is also called elephant creeper. Almost all the parts of the plant like the roots, leaves and the seeds are used in ayurveda for its medicinal purposes. The aim of this study was to screen and determine significant α amylase inhibition of leaves of A. nervosa .This study was conducted to Alpha amylase inhibitory activity of different concentrations of ethanol extracts of A. nervosa leaves were assessed. The extract showed an IC50 value of 143.5 µg/ml. Acarbose was used as a reference standard. The Inhibiting of α amylase enzyme can regulate postprandial hyperglycemia and reduce the risk of developing diabetes